COPD treatment case II: COPD with asthma as child - Kocks, Janwillem (Henry Stewart Talks, 2016)
Asthma-COPD overlap syndrome, LAMA in asthma, Case management, An updated version, which will include the latest GOLD COPD recommendations, will be released in November 2017